Konsep Pemikiran dan Ideologi Ibnu Taimiyah dan Pengaruhnya dalam Perkembangan Sosial-Budaya Masyarakat : Ibn Taimiyah's Concept of Thought and Ideology and Its Influence on the Socio-Cultural Development of Society - Muhammad Ikhsan; Azwar, Azwar (DIRASAH: Jurnal Kajian Islam, 2024)
The development and socio-cultural change of society is inevitable. Many variables become a source of influence within the change. Amongst these variables is human's ideological understandings. The purpose of this study is to reveal the concept by Ibn Taimiyah in understanding and placing Islamic ideology as the foundation for answering socio-cultural change and development in society. The concept was explored through literature studies, while the influence of that concept is examined through of historical study of the origin of Modern Islamic Revival Movement and the establishment of the Kingdom of Saudi Arabia.